Update on autoimmune polyendocrine syndromes (APS) - Betterle, C.; Zanchetta, R. (Acta Biomedica Atenei Parmensis, 2003)
Autoimmune Polyendocrine Syndromes (APS) were initially defined as a multiple endocrine gland insufficiency associated to an autoimmune disease in a patient. Neufeld & Blizzard (1980) suggested a classification of APS, based on clinical criteria only, describing four main types. APS-1 is characterized by presence of chronic candidiasis, chronic hypoparathyroidism, Addison’s disease. It is a very rare syndrome interesting young subjects correlating to different mutations of AIRE (AutoImmuneRegulator) gene on chromosome 21. APS-2 is characterized by presence of Addison’s disease (always present), autoimmune thyroid diseases and/or type 1 diabetes mellitus. It is a rare syndrome interesting particularly adult females and associated to a genetic pattern of HLA DR3/DR4. Autoimmune thyroid diseases associated to other autoimmune diseases (excluding Addison’s disease and/or hypoparathyroidism), are the main characteristics of APS-3. The different clinical combinations of autoimmune diseases not included in the previous groups are characteristics of APS-4. In this paper criteria for defining a disease as autoimmune are presente. Furthermore, the classification, epidemiology, pathogenesis, genetic, animal models, clinical features, laboratory’s tests, imaging, therapy, recent progresses in understanding the APS and a detailed analysis of large group of our patients affected by different types of APS are proposed and discussed.